DEVELOPMENT OF SCIENTIFIC MONOGRAPHY PROJECT ON "AXONOMETRY" (Conferencea, 2022)
Observations show that the knowledge, skills and competencies in graphics are widely used, especially when professionals are working on a new product project. At this stage, the creative specialist makes extensive use of a type of image, especially called axonometric projections.